Dinamika Ruang Pkl Alun-Alun Ponorogo : Sebuah Kearifan Lokal - Hanafi, Achmad Faried; Wulandari, Lisa Dwi; Antariksa, Antariksa (RUAS, 2015)
Nowadays most of alun-alun turned into an urban park that serves as public open space advocates social, aesthetic and ecological functions. PKL as an economic entity, do not lose on the chance of crowd people on public space as a potential market for their business. The existence of street vendors in the square had become a dilemma, allowed or prohibited. This research aims to describe the spatial dynamics of street vendors in alun-alun Ponorogo and explore its existence to study its local wisdom. This study used qualitative descriptive method based on indepth interview on keypersons. The existence of street vendors in alun-alun Ponorogo form spatial-dynamic and as a form of local wisdom that develops in alun-alun Ponorogo.Keywords : alun-alun, Ponorogo, PKL (street vendors), local wisdom